The GRIN Approach: Minimizing Disruptive Behaviors and Increasing Academic Engagements - MARY ELAINE P. ESPELA; EPIFANIA S. DELA CRUZ; RICHARD J. SANTIAGO (International Journal on Orange Technologies, 2021)
Learners cannot learn in chaos. Teachers as facilitators of learning is also the classroom manager. Numerous research and studies have correlated that positive classroom management is vital for effective teaching and learning to happen. Studies also showed that disruptive behaviors inside the classroom will be a great hindrance for learning if not addressed properly. On the other hand, studies have also shown that corporal punishment or punitive approaches to disruptive behavior have cause more harm rather than to solve the problem. These negative responses were able alleviate and not decrease the learners sense of responsibility with their actions. Inflicting fear within them is not an effective solution to stop the learners misbehaviors..